Tinidazole mouth rinse for the treatment of oral lichen planus: an observational pilot study - Ruru Shao; Zhenyuan Wang; Chenglong Yang; Lei Pan; Xu Chen; Guanhuan Du (BMC, 2024)
Abstract Background Given the limited treatment options available for oral lichen planus (OLP), a study was undertaken to obtain preliminary information on the therapeutic efficacy of tinidazole mouth rinse in patients with OLP. Methods A prospective, open-label pilot study was conducted to assess the efficacy of thrice-daily tinidazole mouth rinse for one week in OLP patients (n = 27). Reticulation/erythema/ulceration (REU) scores and visual analog scale (VAS) scores were used to measure lesions at baseline and after one week of treatment. Mucosal samples were collected, and the abundance of Fusobacterium nucleatum was quantified using RT-PCR. Statistical analysis using t-test, Wilcoxon signed rank test and Pearson correlation test. Results After treatment, VAS scores significantly decreased in both reticular (P = 0.03) and erosive OLP patients (P = 0.003). However, REU scores significantly decreased only in erosive OLP patients (P = 0.002). The relative abundance of Fusobacterium nucleatum on the damaged mucosa surface significantly decreased in all OLP patients (P = 0.01). In erosive OLP patients, the triamcinolone group showed a significantly greater improvement in VAS scores compared to the tinidazole group (P = 0.01). However, there was no statistically significant correlation between the relative abundance of Fusobacterium nucleatum and REU scores in OLP patients (r = 0.0754, P = 0.61). Conclusion Tinidazole mouth rinse showed potential in reducing disease severity in OLP patients and was well-tolerated, suggesting its viability as a local therapeutic option. However, randomized controlled studies are warranted to confirm these preliminary findings.